2013
DOI: 10.1177/0042098013482506
|View full text |Cite
|
Sign up to set email alerts
|

Keeping People in Their Place? Young-Adult Mobility and Persistence of Residential Segregation in US Metropolitan Areas

Abstract: Prior research has shown that neighbourhood racial and income contexts remain similar across generations within White, Black and Latino families in the US. This article builds on this research by examining the extent to which geographical mobility during the transition to adulthood attenuates the perpetuation of residential segregation from Whites among Asians, Blacks and Latinos. Data from the National Education Longitudinal Study linked to 1990 and 2000 US census data were analysed. Results suggest that resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Similarity between childhood neighborhood characteristics and the characteristics of neighborhoods inhabited during young adulthood could be driven in part by simple geographic proximity, since young adults often establish their first household near their parents’ home (Sharkey 2008). Growing up in a neighborhood characterized by a particular racial composition could also shape youths’ preferences for the racial composition of their neighborhoods they inhabit later in life (Britton and Goldsmith 2013). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarity between childhood neighborhood characteristics and the characteristics of neighborhoods inhabited during young adulthood could be driven in part by simple geographic proximity, since young adults often establish their first household near their parents’ home (Sharkey 2008). Growing up in a neighborhood characterized by a particular racial composition could also shape youths’ preferences for the racial composition of their neighborhoods they inhabit later in life (Britton and Goldsmith 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Second, growing up in a disadvantaged neighborhood is likely to impair the development and accumulation of the human and financial capital that might facilitate geographic moves to more prosperous neighborhoods in later life (e.g., Corcoran et al 1992; Galster et al 2007; Wodtke, Harding, and Elwert 2011). And third, exposure to neighborhoods of a given racial composition during childhood might shape individuals’ preferences for the racial composition of the neighborhoods they inhabit in later life (Britton and Goldsmith 2013; Marsh et al 2011). But few studies have examined how adolescent neighborhood experiences are associated with neighborhood contexts in mid-to-late adulthood, and thus it is unknown how long the “effects” of adolescent neighborhood contexts on subsequent neighborhood contexts last.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…If left unchallenged, racial segregation is likely to persist. In a longitudinal study of housing mobility in major metropolitan areas, Britton and Goldsmith (2013) found that limited exposure to integrated neighborhoods during adolescence was a predictor of living in a segregated neighborhood later in life. More specifically, people of color who lived in segregated neighborhoods in their youth were more likely to live in segregated communities as adults.…”
mentioning
confidence: 99%
“…A number of longitudinal studies have evaluated hypotheses related to neighborhood residence and the findings lead to a number of conclusions: (a) living in a neighborhood with high levels of poverty as a child is strongly associated with living in a neighborhood with high levels of poverty as an adult; (b) life course events such as graduating high school, getting married, the birth of a child, and buying a home are significantly related to changes in one's residential environment; and (c) a person's socioeconomic status, especially income, significantly affects the probability of living in an economically depressed area (Britton & Goldsmith, ; Coulter & Van Ham, ; Sampson & Sharkey, ; Sharkey, , ; South, Huang, Spring & Crowder, ; South et al., ; Swisher, Kuhl & Chavez, ; Wagmiller, ).…”
Section: Residential Mobility and Neighborhood Residencementioning
confidence: 99%